Has fertility declined in recent decades? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Purpose of review Over the last decade, a number of studies have been published on whether fertility has declined. The purpose of this article is to review the trends in fertility rates and assess how biological, behavioural, social and environmental factors affect fertility rates. Recent findings The average total fertility rate (TFR) in Europe is down to 1.5 children per woman, and the perceived ideal family size is also declining. Factors impacting on lower fertility include the instability of modern partnerships and value changes. Fertility depends on natural fecundity but also on a number of behavioural determinants, such as culture, society, economic conditions, living standards and other similar background determinants on individual reproductive behaviour. Summary Increasing use of infertility treatment and a decline in demographic fertility in some countries have raised concern whether human fecundity is declining or has declined over time. The downward trend in fecundity articulated on numerous occasions over the last decade, seems unsubstantiated as the forecasting agencies such as the United Nations and Eurostat are likely to be right in their medium variant assumption that TFR levels in most countries will rise to 1.5 or above in the decades ahead.
Keywords: demography; fertility; fertility decline; pregnancy; total fertility rate; TIME TRENDS; FAMILY POLICY; CHILDBEARING; PREGNANCY; IMPACT; QUESTIONNAIRE; FECUNDABILITY